DESCRIPTIVE LANDSCAPES:RECORDING POSSIBLE PLACES ON THE WORK OF FRANS POST (1612-1680) (Palíndromo, 2018)
This article analyzes three works by the Dutch artist Frans Post (1612-1680), a member of the scientific mission brought by Count Maurício de Nassau to Brazil in the 17th century. The works - called The River São Francisco (1638), Forte Maurício on the São Francisco River (1647) and Paulo Afonso Waterfall (1647) - are simultaneously approached from a scientific perspective and as pictorial representations. The notion of possible places, as proposed by Svetlana Alpers (1987), is developed aiming the understanding of the images created by Post in loco as a traveling artist and, later, of the representations created from the repertoire of forms, constituted during his stay in Brazil. In this way, it is intended to broaden the understanding of the artist’s work, maintaining its dual status, as descriptive visual records and as images constructed between reality and artifice.
Keywords: Frans Post; descriptive landscape; recording; possible places